Identification of Novel Immune and Barrier Genes in Atopic Dermatitis by Laser Capture Micro-dissection - Esaki, Hitokazu (J Allergy Clin Immunol, 2015)
BACKGROUND: The molecular signature of atopic dermatitis/AD lesions is associated with Th2 and Th22 activation, and epidermal alterations. However, the epidermal and dermal AD transcriptomes and their respective contributions to abnormalities in respective immune and barrier phenotypes are unknown. OBJECTIVE: To establish the genomic profile of the epidermal and dermal compartments of lesional/LS and non-lesional/NL AD, as compared with normal skin. METHODS: Laser capture micro-dissection/LCM was performed to separate epidermis and dermis of LS and NL skin from AD patients and normal skin from healthy volunteers followed by gene expression (microarrays and RT-PCR) and immunostaining studies. RESULTS: Our study identified novel immune and barrier genes, including the IL-34 cytokine and claudins 4 and 8, and showed increased detection of key AD genes usually undetectable on arrays (i.e. IL-22, TSLP, CCL22, and CCL26). Overall, the combined epidermal and dermal transcriptomes enlarged the AD transcriptome adding 674 up-regulated and 405 down-regulated differentially expressed genes between LS and NL skin to the AD transcriptome. We were also able to localize individual transcripts as primarily epidermal (DEFB4A) or dermal (IL-22, CTLA4, and CCR7), and link their expressions to possible cellular sources. CONCLUSIONS: This is the first report that establishes robust epidermal and dermal genomic signatures of LS, NL AD and normal/N skin, as compared with whole tissues. These data establish the utility of LCM to separate different compartments and cellular subsets in AD, allowing localization of key barrier or immune molecules, and enable detection of gene products usually not detected on arrays.